2014
DOI: 10.3171/2014.4.focus1467
|View full text |Cite
|
Sign up to set email alerts
|

Operative and nonoperative adverse events in the management of traumatic fractures of the thoracolumbar spine: a systematic review

Abstract: Object Thoracolumbar spine injuries are commonly encountered in patients with trauma, accounting for almost 90% of all spinal fractures. Thoracolumbar burst fractures comprise a high percentage of these traumatic fractures (45%), and approximately half of the patients with this injury pattern are neurologically intact. However, a debate over complication rates associated with operative versus nonoperative management of various thoracolumbar fracture morphologies is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 47 publications
1
38
1
3
Order By: Relevance
“…Ghobrial et al reported that burst fractures constitute as high as 45% of all thoracolumbar fractures (13). Another study by Been and Bouma reported a rate of 49% (4).…”
Section: █ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ghobrial et al reported that burst fractures constitute as high as 45% of all thoracolumbar fractures (13). Another study by Been and Bouma reported a rate of 49% (4).…”
Section: █ Discussionmentioning
confidence: 98%
“…Distinctive factors in the treatment of traumatic spinal fractures can be defined as the presence of neurological deficit and progression of the regarding injury (7). It is widely accepted that a relatively urgent surgical approach might be associated with decreased risk of complications regarding immobility (5,13,22). On the other hand, preservation of critical life measures after systemic trauma aids in balanced systemic status and diminished risk of successive interventions.…”
Section: █ Introductionmentioning
confidence: 99%
“…Conservative treatments or surgery and commonly accepted procedures for vertebral fractures . However, these treatment strategies are associated with major postoperative morbidities, such as postoperative embolism, pneumonia, healing failure, kyphosis, and infection . The most severe postoperative complication of vertebral fracture is healing failure, leading to thoracolumbar kyphosis and spinal cord injury, which require revision surgery.…”
mentioning
confidence: 99%
“…4,5 However, these treatment strategies are associated with major postoperative morbidities, such as postoperative embolism, pneumonia, healing failure, kyphosis, and infection. [6][7][8] The most severe postoperative complication of vertebral fracture is healing failure, leading to thoracolumbar kyphosis and spinal cord injury, which require revision surgery. Recently, the potential therapeutic applications of low-intensity pulsed ultrasound (US) have been reported in clinical trials as a noninvasive adjuvant treatment modality in fracture healing.…”
mentioning
confidence: 99%
“…Although some authors believe that in more stable thoracolumbar burst fractures associated with normal neurologic examination, nonoperative treatment provided the same long-term advantages as surgery, in the patients with more severe injuries and neurologic deficit, early fusion and instrumentation can promote earlier mobilization and neurologic rehabilitation [4][5][6][7]. In spinal surgery of lumbar area, literature reveals that spondylodesis of the freely moving lumbar vertebrae is strongly correlated with functional disability in activities of daily living [8].…”
Section: Introductionmentioning
confidence: 99%